Four-Leaf Clover Shape Agglomerate Keratoacanthomas: A Case Report - Yang D; Mao Y; Peng L; Huang S; Zhou L; Li C (Dove Medical Press, 2024)
Dingbin Yang,1,2 Yu Mao,3 Lu Peng,2 Shuqiong Huang,2 Lijun Zhou,2 Changqiang Li1 1Department of Dermatology, the Affiliated Hospital, Southwest Medical University, Luzhou, 646000, People's Republic of China; 2Department of Dermatology, People's Hospital of Leshan, Leshan, 614000, People's Republic of China; 3Department of Pathology, People's Hospital of Leshan, Leshan, 614000, People's Republic of ChinaCorrespondence: Changqiang Li, Department of Dermatology, the Affiliated Hospital, Southwest Medical University, Luzhou, 646000, People's Republic of China, Email lcq-1973@163.comAbstract: Keratoacanthoma (KA) is a papule, plaque, or nodule in an exposed area, with a crater-like horn plug in the center. Multiple KAs are rare disorders, especially when the lesions are agglomerated together. Herein, we report a case of 65-year-old man who presented with four red nodules of different sizes on the right side of the chest. The lesions were clustered, with central keratotic cores, similar in appearance to a four-leaf clover. The nodules were completely removed by excisional surgery and the diagnosis of Agglomerate KAs was made based on clinical and pathological results. A 6-year follow-up found no recurrence.Keywords: agglomerate keratoacanthomas, four-leaf clover